PERLINDUNGAN HUKUM BAGI PENYEBAR KONTEN MEDIA SOSIAL YANG MENGANDUNG TINDAK PIDANA - Gusti Erlangga JF; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This research discusses the Legal Protection of Social Media Content Spreaders that Contain Crimes. Legal protection is an act to protect the interests of legal subjects with the rules or rules that apply to the person to take action that can meet their interests. Based on Article 27 paragraph (3) of the Transaction and Electronic Information Act, hereinafter referred to as ITE, states that it prohibits anyone from deliberately and without the right to distribute and / or transmit and / or make access to Electronic Information and / or Electronic Documents that have an insulting content. and / or defamation. The purpose of writing this thesis, namely; First, to find out Legal Protection for Social Media Content Spreaders Containing Criminal Acts, Second, To find out the ideal settings in providing Legal Protection for Social Media Content Spreaders that Contain Crimes.The type of legal research used by the author is a type of normative research. Normative legal research uses primary data and secondary data. Data collection techniques in this study with library research literature.From the results of this study the authors conclude that legal protection for disseminating social media content that contains criminal acts is seen from the freedom of expression and believes there are still some rights that are violated. The ideal arrangement in providing legal protection for disseminators of social media content that contains criminal acts is not so optimal in Indonesia.Keywords: Content Spreader - Criminal Actions - Legal Protection